Linguostatistical Analysis Of Toponyms Formed With Color Terms In The Uzbek Language - Ismаtоvа Nоdirаxоn mаxmudоvnа (European International Journal of Pedagogics, 2026)
This study examines toponyms formed with color terms in the Uzbek language using a linguostatistical approach. Based on a corpus of 1,200 place names, including 312 with color components, the research identifies their frequency, structural patterns, and semantic features. The results show that oq (white) and qora (black) are the most productive elements, reflecting both physical characteristics and cultural-symbolic meanings. The study highlights the interaction between language, culture, and geography in Uzbek toponymy and contributes to linguocultural and onomastic research.